The Internalization of Independence to mentally-disabled Child through Self-Development Learning - Firdha Hayati (Tajdid Al-Athfal, 2021)
Self-development learning in mentally disabled children is still not fully realized by the community. Children with mental disabled have difficulty taking care of themselves so they need the help of others. Therefore, they need training to develop their self-development skills so that later they can be independent. This research aims to describe the internalization of independence to mentally-disabled child through self-development learning in one of inclusive Early Childhood Education at Yogyakarta. The research was conducted by conducting observation to the child and interviews to the guide teacher. The results of this study indicate that significantly mentally disabled child in the span of 1 year have begun to show progress in terms of self-development. This can be seen that she understands the instructions from her teacher, can already express what she feels, and has started to be able to eat with her cutlery